Abrasive wear of FeCr (M7C3-M23C6) reinforced iron based metal matrix composites - Yilmaz, O (I O M Communications Ltd Inst Materials, 2001)
The effects of volume fraction, particle size, and sintered porosity of FeCr (M7C3-M23C6) particulates on the abrasive wear resistance of powder metallurgy (PM) Fe alloy metal matrix composites have been studied under different abrasive conditions. It was seen that the abrasive wear rate of the composites increased with an increase in the FeCr volume fraction in tests performed with 80 grade SiC abrasive paper, but it decreased for tests conducted with 220 grade SiC abrasive paper. Furthermore, the wear rates decreased with an increase in FeCr size for composites containing the same amount of FeCr. Hence it is deduced that Fe alloy composites reinforced with larger size FeCr particles are more effective against abrasive wear than those reinforced with smaller ones. At the same time the results show that the beneficial effects of hard FeCr particulates on wear resistance far outweighed the detrimental effects of sintered porosity in the PM metal matrix composites. In addition, the fabrication of composites containing soft particles such as graphite or copper favours a reduction in the coefficient of friction, and increases the matrix hardness of the composite. For this reason graphite and copper were used in the matrix in different amounts to test their effect on the wear resistance. Increase in graphite and copper volume fraction allowed the formation of additional phases, which had high hardness and wear resistance. It was also found that the wear rate of the composites decreased considerably with graphite and copper addition. (C) 2001 IoM Communications Ltd.
Keywords: Particle Composites; Aluminum-Alloys; Fabrication; Solidification; Mechanisms; Behavior